Mineral nutrients in the shoot biomass of soil cover crops - Borkert, Clóvis Manuel; Gaudêncio, Celso de Almeida; Pereira, José Erivaldo; Pereira, Leonardo Régis; Junior, Adilson de Oliveira (Pesquisa Agropecuaria Brasileira, 2003)
The objective of this work was to estimate the quantity of nutrients recycled by five species of cover crops and returned to the soil after the mineralization of the biomass. Fresh samples of several experiments of black oats (Avena strigosa Schreb), black mucuna (Stizolobium aterrimum Piper & Tracy), pigeon pea (Cajanus cajan (L.) Millsp), lupin (Lupinus albus L. and L. angustifolius L.) and common vetch (Vicia sativa L.) were taken to estimate dry matter yield and determine the content of N, P, K, Ca, Mg, Mn, Zn, and Cu. From the dry matter yield, nutrient content were analyzed, and the estimated and observed mean, and a confidence limit at the 95% level, for each nutrient, in each class of dry matter yield and in each cover crop species were calculated. The data were tabulated with the corresponding dry matter class intervals and estimated quantity of nutrients. Equations were adjusted to estimate the quantity of nutrients in relation to dry matter yield. Black oats and common vetch, are good for recycling K, and common vetch, black mucuna, lupin and pigeon pea recycled large amounts of N. All species recycled large amounts of Ca, Mg and micronutrients, but small amounts of P. Crop rotation is a way of successfully increasing field areas under no-tillage.
Keywords: protective plants; nutrient recycling; mineralization; rotational cropping